2018
DOI: 10.1093/ecco-jcc/jjy049
|View full text |Cite
|
Sign up to set email alerts
|

Andecaliximab [Anti-matrix Metalloproteinase-9] Induction Therapy for Ulcerative Colitis: A Randomised, Double-Blind, Placebo-Controlled, Phase 2/3 Study in Patients With Moderate to Severe Disease

Abstract: Background and AimsMatrix metalloproteinase-9 [MMP9] is implicated in the pathogenesis of ulcerative colitis [UC] via disruption of intestinal barrier integrity and function. A phase 2/3 combined trial was designed to examine the efficacy, safety, and pharmacokinetics of the anti-MMP9 antibody, andecaliximab [formerly GS-5745], in patients with moderately to severely active UC.MethodsPatients were randomised [1:1:1] to receive placebo, 150 mg andecaliximab every 2 weeks [Q2W], or 150 mg andecaliximab weekly [Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 48 publications
0
32
0
1
Order By: Relevance
“…We also found evidence through cis-MR of a causative role for MMP9 in CD and IBD. Recent phase 2 trials failed to demonstrate efficacy of andecaliximab, a monoclonal antibody targeting MMP9 in either UC or CD 33,34 (Fig. 6).…”
Section: Pcsk9mentioning
confidence: 99%
“…We also found evidence through cis-MR of a causative role for MMP9 in CD and IBD. Recent phase 2 trials failed to demonstrate efficacy of andecaliximab, a monoclonal antibody targeting MMP9 in either UC or CD 33,34 (Fig. 6).…”
Section: Pcsk9mentioning
confidence: 99%
“…Hence, it was suggested that MMP9 mAb has therapeutic potential for the treatment of CIPN. Importantly, a humanized MMP9 antibody (andecaliximab) has reached advanced clinical trials for the treatment of colitis (ClinicalTrials.gov: NCT02405442) [139,140] and alimentary tract cancer (ClinicalTrials.gov: NCT01803282) [141,142]; hence, it may also be repurposed for CIPN [143].…”
Section: Future Outlook: Data From Preclinical Studiesmentioning
confidence: 99%
“…A randomized placebo controlled phase 1b single and multiple ascending dose-ranging clinical trial on 72 patients diagnosed with moderately to severely active ulcerative colitis (UC) showed that GS-5745 was safe, well-tolerated, and could be used as a potential therapeutic agent for UC (77). A phase 2/3 UC study with 165 patients treated over 8 weeks further indicated that GS-5745 was well-tolerated (78). A phase 1b trial investigating the safety, pharmacokinetics, and disease-related outcomes for 15 rheumatoid arthritis patients (ClinicalTrials.gov Identifier NCT02176876) demonstrated that GS-5745 was safe, with adverse events that were only grade 1 or 2 in severity and no indication of MSS (79).…”
Section: Mmp-9 Selective Inhibitorsmentioning
confidence: 99%